Eczacılıkta Güncel Araştırmalar III-Güz - Küçük, Ege; Akman, Tuğrul Çağrı; Dehri, Ömer Faruk; Sevinç Özakar, Rukiye; Özakar, Emrah; Alparslan, Bayram; Özçelik, İbrahim and Özdal, Zeliha Duygu and Yıldıztekin, Kübra Gizem and Vural, Meltem and Küçük, İrem Sena and Türkmen, Neşe Başak and Yumşak, İsmail and Toku, Elif and Alptekin, Özlem and Bulut, Ayşe Selenga and Çiçek, Figen and Büyüknacar, H. Sinem and Bayındır, Süleyman Burak and Karahüseyin, Seçil (Academician Publishing Book DOI Portal, 2024)
-